Evaluation of EIGRP IPv6 and RIPng Effectiveness on IPv6 Networks with EVE-NG Emulator - Pebriyanti, Cahyani; Ichsan, Ichwan Nul (Aviation Electronics, Information Technology, Telecommunications, Electricals, and Controls (AVITEC), 2025)
This study aims to evaluate the performance of two IPv6 routing protocols, namely EIGRP and RIPng, based on Quality of Service (QoS) parameters such as throughput, packet loss, and delay on a network with a configuration of two routers and five routers. The method used is Design Science Research Methodology (DSRM), which includes literature review, network simulation design, data collection, and analysis. Tests were conducted using the EVE-NG simulator and Wireshark to analyze network traffic. The results show that EIGRP has a higher throughput than RIPng, with an average throughput of 3910 bit/s on two routers and 4118 bit/s on five routers, while RIPng recorded a throughput of 3594 bit/s and 4090 bit/s on the same configuration. In addition, EIGRP also showed a lower delay of 999 ms in both configurations, compared to RIPng which recorded a delay of 1570 ms for two routers and 1530 ms for five routers. Both protocols had similar results on the packet loss parameter (0%). These findings indicate that EIGRP is more efficient in maintaining throughput stability and reducing delay, thus it is superior in providing responsive network performance, even with a larger number of routers.